Trait and state-related characteristics of thalamo-cortical circuit disruption in bipolar disorder: a prospective cross-sectional study - Zeng, Can; Liao, SuQun; Pu, Weidan (Frontiers in Psychiatry, 2023)
Objective: The purpose of this study is to investigate the shared and distinct thalamic-cortical circuit between bipolar depression and remission, as well as to investigate the trait and state-related characteristics of the abnormal thalamic-cortical circuit in bipolar disorder. Methods: Resting-state functional magnetic resonance imaging was performed on 38 bipolar depression patients, 40 bipolar remission patients, and 39 gender-matched healthy controls (rsfMRI). The thalamic subregions were used as seed points to draw the functional connectivity of the entire brain, and then the shared and distinct thalamic-cortical circuits between bipolar depression and remission were compared. Results: When compared to the healthy group, both groups of patients had significantly lower functional connectivity between the rostral temporal thalamus and the lingual gyrus, the posterior parietal thalamus, the precuneus/cerebellum, and the occipital thalamus and the precuneus; however, functional connectivity between the premotor thalamus and the superior medial frontal was significantly lower in depression. Conclusion: This study discovered that both bipolar depression and remission had abnormal sensorimotor-thalamic functional connectivity, implying that it is a trait-related characteristic of bipolar disorder; however, the decline in prefrontal-thalamic connectivity exists specifically in bipolar depression, implying that it is a state-related characteristic of bipolar disorder